Interpretation of Hermeneutics and Religious Normativity (Hermeneutic Approach in Scientific Studies in the Islamic World) - Sya'bani, Mohammad Ahyan Yusuf (IJISH (International Journal of Islamic Studies and Humanities), 2019)
The clergy have long used the method of hermeneutics in the 17th century to interpret classical texts in a meaning. Because of this, in the study of scientific knowledge, Islam tries to use hermeneutical interpretations to find a meaning that can be understood easily by humans. So the need to do a research on the above issues to find formulations and hermeneutic methods in Islamic scholarship that not only consists of the holy book of the Qur'an and al-Hadith as authentic texts but also thoughts, culture, fiqh, theology and fields of science others in Islam. This research method is a study with a type of literature study (literature study) with a philosophical-historical approach .Data collection techniques with documentation techniques. The results of the study show that Muslim scholars such as Amin Abdullah try to use the hermeneutic method in Islamic studies to produce scientific assumptions in Islamic studies, namely , first, the nature of knowledge summarized in various studies is not fixed and static, but dynamic; secondly, the thinking carried out by the scholars' is the result of the interaction between the text (al-Qur`an and Sunnah) and the social context that surrounds it; third, full emphasis on the empirical-critical paradigm for conducting religious reviews, including thoughts about the sacredness of the text itself, and the results of that thought are not fixed, but always changing.